2006
DOI: 10.1007/s00167-006-0042-9
|View full text |Cite
|
Sign up to set email alerts
|

Continuous passive motion following total knee replacement: a prospective randomized trial with follow-up to 1 year

Abstract: We have carried out a prospective randomised, single blind clinical trial to investigate the effect of continuous passive motion on range of knee flexion, lack of extension, pain levels and analgesic use after total knee replacement surgery. 85 subjects were randomly allocated to control or study group. All subjects followed the existing rehabilitation protocol, which permits immediate active range of motion exercises and mobilisation with the study group using continuous passive motion for 1 h, twice a day. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1
24

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 23 publications
3
30
1
24
Order By: Relevance
“…However, the authors also highlighted the need for further research about the use of CPM, because of its inconvenience and expense, and put the question about the determination of protocols concerning the duration and intensity of CPM application [28] . Following this study, Leach et al [29] in 2006 published a prospective randomized trial, with a 1-year follow-up, in which they concluded that CPM does not offer significant benefits in range of knee motion and pain, after the application of a specific CPM protocol. This publication initiated a series of highquality studies, which, since then, have contested the use of CPM after TKA.…”
Section: Cpm: To Use or Not To Use?mentioning
confidence: 95%
See 1 more Smart Citation
“…However, the authors also highlighted the need for further research about the use of CPM, because of its inconvenience and expense, and put the question about the determination of protocols concerning the duration and intensity of CPM application [28] . Following this study, Leach et al [29] in 2006 published a prospective randomized trial, with a 1-year follow-up, in which they concluded that CPM does not offer significant benefits in range of knee motion and pain, after the application of a specific CPM protocol. This publication initiated a series of highquality studies, which, since then, have contested the use of CPM after TKA.…”
Section: Cpm: To Use or Not To Use?mentioning
confidence: 95%
“…CPM use or not for computer-assisted TKA No statistically significant difference in flexion, edema or drainage, function, or pain between groups 3 mo post-surgery Lensenn et al [31] Randomised controlled trial. Effectiveness of prolonged CPM use vs in hospital only use of CPM No long term difference in ROM or any of the outcome assessments Leach et al [29] Prospective randomized trial investigating the effect of CPM on range of knee flexion, lack of extension, pain levels and analgesic use after TKR…”
Section: No Evidence That Cpm Reduces Vte After Tkrmentioning
confidence: 99%
“…• GC (19): recibió fisioterapia convencional más CPM. 30 minutos/día desde postoperatorio durante 3 semanas.…”
Section: Medidasunclassified
“…Siendo la mayor muestra, N= 170, del trabajo realizado por Chen y col 14 y la menor muestra, N=38, la utilizada en la investigación de Mau-Moeller A. y col 15 . En todos los trabajos analizados se tomaron medidas en cuanto al rango de movilidad articular, tanto en flexión como extensión [14][15][16][17][18][19][20][21][22][23][24][25] . El dolor fue el segundo parámetro más estudiado, siendo valorado en todos los trabajos excepto en los realizados por Lenssen y col 16 , Herbold y col 17 y Davies y col 18 .…”
Section: Descripción De Los Artículosunclassified
See 1 more Smart Citation